DIGITALIZATION PROBLEMS IN THE DEVELOPMENT OF SERVICE PROVISION BASED ON PRIVATE ENTREPRENEURSHIP - Boboqulov Sanjar Baxronkulovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article analyzes the role and significance of digitalization in the development of services based on private enterprise. The introduction of modern technologies into the service sector contributes to increased business efficiency and the creation of more convenient customer service opportunities. The article examines the application of digitalization processes in business, methods for improving the efficiency of service delivery through digital technologies, and the challenges that arise in this regard.